Nursing imbuted in the healthcare world and the feelings of people - Cervera Vallejos, Mirtha Flor (2023)
Care is a fundamental task for the promotion of the common good of society, where the ethical mark is given by solidarity, and since being in the health world is going further, it is a challenge to promote it within public policies because this is not It is a burden for the people, nor for the state, but as described at the beginning, it reflects being in the efforts of everyone within a society cultured by solidarity, where friendly treatment stands out without excluding anyone.